Positional Change of the Eyeball During Eye Movements: Evidence of Translatory Movement - Moon, Yeji; Lee, Won June; Shin, Seung Hak; Kim, Ji Hong; Lee, Ji Young; Oh, Sei Yeul; Lim, Han Woong (Frontiers in Neurology, 2020)
Purpose: To investigate the positional change of the eyeball induced by horizontal and vertical gazing to deduce translatory movement, using three-dimensional (3D) magnetic resonance imaging (MRI). Methods: In this prospective observational study participants underwent orbital MRI during central, right, left, up, and down gazing. MRI scans were processed using self-developed software; this software enabled 3D MR image reconstruction and the superimposition of reconstructed image sets between different gazes. After acquiring the coordinates of the eyeball centroid in each gaze, the changes in centroid coordinates from central gaze to the other gazes were estimated, and correlations with associated factors were evaluated. Results: The mean distance of centroid movement in was 0.69 ± 0.27 mm in abduction, 0.68 ± 0.27 mm in adduction, 0.43 ± 0.23 mm in elevation and 0.44 ± 0.19 mm in depression. The mean angle of centroid movement in horizontal gaze, measured in terms of the movement of the left eye centroid in the axial plane, was 228.7º in abduction and −4.2º in adduction. In vertical gaze, the mean angle of centroid movement was −96.8º in elevation and 101.8º in depression. Axial length and ocular volume were negatively correlated with the distance of centroid movement in horizontal gaze. Conclusions: The position of the eyeball moved in the same direction as the gaze during horizontal gaze, but in the opposite direction during vertical gaze. For accurate eye movement analyses, such as the measurement of the deviation angle in strabismus, translation should be considered in addition to rotation.